2015
DOI: 10.3390/ijms160820067
|View full text |Cite
|
Sign up to set email alerts
|

Variants of MicroRNA Genes: Gender-Specific Associations with Multiple Sclerosis Risk and Severity

Abstract: Multiple sclerosis (MS) is an autoimmune neuro-inflammatory disease arising from complex interactions of genetic, epigenetic, and environmental factors. Variations in genes of some microRNAs—key post-transcriptional regulators of many genes—can influence microRNAs expression/function and contribute to MS via expression changes of protein-coding target mRNA genes. We performed an association study of polymorphous variants of MIR146A rs2910164, MIR196A2 rs11614913, MIR499A rs3746444 MIR223 rs1044165 and their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 50 publications
(70 reference statements)
2
19
0
5
Order By: Relevance
“…Many studies have suggested that rs3746444 is correlated with the incidence and risk of many cancers in Asian populations , including prostate cancer (PCa) , squamous cell carcinoma of the head and neck (SCCHN) , and breast cancer , while the relationship between rs3746444 and non‐HBV‐related hepatocellular carcinoma (HCC) has not been discovered . rs3746444 may be involved in inflammatory AD, such as rheumatoid arthritis (RA) , Behcet's disease (BD) , and multiple sclerosis (MS) , by regulating various inflammatory factors. The T allele of rs3746444 was a risk factor in an Iranian population compared with the C allele, while it was a protective factor in Mediterranean populations, and Yang et al found it had no effect in an Asian population for RA .…”
Section: Mirna‐137mentioning
confidence: 99%
“…Many studies have suggested that rs3746444 is correlated with the incidence and risk of many cancers in Asian populations , including prostate cancer (PCa) , squamous cell carcinoma of the head and neck (SCCHN) , and breast cancer , while the relationship between rs3746444 and non‐HBV‐related hepatocellular carcinoma (HCC) has not been discovered . rs3746444 may be involved in inflammatory AD, such as rheumatoid arthritis (RA) , Behcet's disease (BD) , and multiple sclerosis (MS) , by regulating various inflammatory factors. The T allele of rs3746444 was a risk factor in an Iranian population compared with the C allele, while it was a protective factor in Mediterranean populations, and Yang et al found it had no effect in an Asian population for RA .…”
Section: Mirna‐137mentioning
confidence: 99%
“…De acordo com Kiselev et al, (2015), os miRNAs são pequenas sequências de RNA de fita simples com tamanho entre 19-24 nucleotídeos. Atualmente estão depositadas no miRBase (http://www.mirbase.org/) mais de 1800 miRNAs humanos que foram descobertos.…”
Section: Expressão E Função Dos Mirnas Na Emunclassified
“…Segundo Kiselev et al (2015) a presença de diferentes miRNAs foi demostrada de forma alterada em pacientes com esclerose múltipla.…”
Section: Fonte: (Zhou Et Al 2014)unclassified
“…Deux théories qui s'opposent l'une à l'autre, émergent. La première considère la dérégulation des miARN comme un des facteurs responsables de l'apparition de la SEP. À l'appui de cette théorie, la mise en évidence récente de l'association entre SEP et certains variants génétiques de miARN [9,10]. La seconde théorie suppose que la dérégulation des miARN serait une conséquence d'un dérèglement préalable de la réponse neuro-immune.…”
Section: Liens D'intérêtunclassified
“…Au début des années 2000, l'importance des miARN a été décrite dans diffé-rents contextes pathologiques (le diabète [6] (➜), les maladies cardiovasculaires [7,58] (➜) et le cancer [8]). Plusieurs équipes se sont alors intéres-sées à l'expression des miARN chez les patients atteints de SEP. D'autres ont étudié les polymorphismes des gènes codant ces miARN : des polymorphismes mononucléo-tidiques (ou SNP pour single nucleotide polymorphism) associés à la SEP ont ainsi été découverts dans certains gènes de miARN [9,10]. Parallèlement, un vaste réseau de miARN, dont l'expression est modifiée chez les patients atteints de SEP, a été mis en évidence, princiconséquence, des recommandations récentes ont proposé de regrouper la PPMS et la SPMS en une seule entité, dénommée « maladie progressive ».…”
unclassified